2020
DOI: 10.3390/ijms21249628
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Arachidonic and Linoleic Acid Derivatives in Pathological Pregnancies and the Human Reproduction Process

Abstract: The aim of the available literature review was to focus on the role of the proinflammatory mediators of AA and LA derivatives in pathological conditions related to reproduction and pregnancy. Arachidonic (AA) and linoleic acid (LA) derivatives play important roles in human fertility and the course of pathological pregnancies. Recent studies have demonstrated that uncontrolled inflammation has a significant impact on reproduction, spermatogenesis, endometriosis, polycystic ovary syndrome (PCOS) genesis, implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 100 publications
(69 reference statements)
1
73
1
Order By: Relevance
“…Finally, omega-3 PUFAs may also have effects on the hormone levels of PCOS patients. Omega-3 PUFAs inhibited the arachidonic acid-induced activation of acute regulatory protein factor and also regulate the expression of LH (12) . In addition, it can regulate testosterone activity in PCOS patients, inhibit testosterone production and produce intervention effects.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, omega-3 PUFAs may also have effects on the hormone levels of PCOS patients. Omega-3 PUFAs inhibited the arachidonic acid-induced activation of acute regulatory protein factor and also regulate the expression of LH (12) . In addition, it can regulate testosterone activity in PCOS patients, inhibit testosterone production and produce intervention effects.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, AA is a precursor of prostaglandin and other metabolites, which play a key role in the late pregnancy period and delivery [ 49 ]. Nevertheless, an excessive activation of inflammatory mediators during pregnancy might lead to deleterious effects, such as gestational diabetes, preeclampsia or pre-term delivery [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have assessed the changes in FA during pregnancy [ 8 10 ]. An appropriate balance with n-3 and omega-6 polyunsaturated fatty acids (n-6 PUFA) is necessary [ 11 , 12 ] because a high concentration of maternal arachidonic acid (AA) has been associated with deleterious outcomes, such as major depression in the mother [ 13 , 14 ], or preterm delivery [ 15 ]. However, a higher maternal AA/DHA ratio at delivery and heterozygosity for the FADS1 genetic variant have shown positive long-term effects on processing speed in children at 9 years of age [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Normally, the production of inflammatory mediators such as AA is associated with the course of pregnancy. However, abnormally high levels have been related to pathological pregnancy complications such as preeclampsia, premature labor, fetal growth, among others (especially in women with risk factors for overweight and obesity) [27]. Some of these complications occur during T3, however Otto et al [14] measured FA during T1.…”
Section: Discussionmentioning
confidence: 99%
“…Delta-6desaturase is predominantly involved in the PUFA biosynthesis pathway and converts LA and alpha-lipoic acid (ALA) into their metabolites DHGLA, AA, EPA and DHA [3,7], although it can also catalyze palmitic acid and stearic acid thus affecting MUFA levels [25]. The n-6/n-3 ratio reflects the predominant PUFA family in serum and the formation of inflammatory mediators, which play important roles in pregnancy pathologies [26,27]. According to the available data, no study has reported reference intervals for serum n-6/n-3, AA/EPA, AA/(EPA + DHA) and LA/DHGLA ratios, or the EFA index in pregnant women.…”
Section: Introductionmentioning
confidence: 99%